Literature Review : Faktor –Faktor yang Mempengaruhi Pola Makan Anak Usia 2-7 Tahun - Ninda Azifati Nurfitri; Rinawati; Vera Yunita; Luvi Dian Afriyani (Universitas Ngudi Waluyo, 2024)
Suboptimal feeding practices and food intake in childhood are associated with poor health outcomes in adulthood. This literature review study aims to profile feeding practices, parental perceptions, and dietary diversity in children aged 2-7 years. The type of research is a study using the Literature Review Study method with the aim of analyzing factors that influence the eating patterns of children aged 2-7 years. The search was conducted electronically using a database from 2020 to 2024. The keywords used were